COMPARISON OF SAFETY FACTOR AND GEOSYNTETIC REINFORCEMENT REQUIREMENT FOR SLOPE STABILITY USING 2-D AND 3-D ANALYSIS METHOD - Sari, Putu Tantri kumala; Lastiasih, Yudhi; Shoffiana , Nur ‘Arfiati (Journal of Applied Engineering Science, 2022)
The analysis of landslide slope stability since 1960s is the development of a 2-D structure proposed by various experts, through the 3-D method. Most of these previous studies stated that the ratio of 3-D and 2-D safety factors was more than one for cohesive and less than one for non-cohesive soils. These were because several required slope reinforcements were affected by the safety factors, with the analytical differences of the 2-D and 3-D methods causing a distinction in the requirements. These differences further cause problems by underestimating or overestimating the design. Therefore, this study aims to determine a comparative analysis of 2-D and 3-D slope stability on several required reinforcements. The analyses of the 2-D and 3-D structures were carried out using the LEM proposed by Fellenius and Hovland, respectively. The comparison of the several required reinforcements was also conducted using geotextile with Tult = 200 kN/m. The results showed that the reinforcements required with geotextile between 2-D and 3-D analysis were relatively similar on homogeneous soils. Meanwhile, the geotextile reinforcement needs were different for heterogeneous soils. Under different certain conditions, the need for 2-D reinforcement was greater and lesser than 3-D. In addition, the difference in the reinforcement required for the analysis of these structures was between 1-8 layers of geotextile, depending on soil parameters, slope, and length of the landslide field.